2018
DOI: 10.3389/fnins.2018.00573
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Distinction of Mild Brain Injury Effects in a Ferret Model Using Diffusion Tensor MRI (DTI) and DTI-Driven Tensor-Based Morphometry (D-TBM)

Abstract: Mild traumatic brain injury (mTBI) is highly prevalent but lacks both research tools with adequate sensitivity to detect cellular alterations that accompany mild injury and pre-clinical models that are able to robustly mimic hallmark features of human TBI. To address these related challenges, high-resolution diffusion tensor MRI (DTI) analysis was performed in a model of mild TBI in the ferret – a species that, unlike rodents, share with humans a gyrencephalic cortex and high white matter (WM) volume. A set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…This is not the focus of our research and does not directly impact on the observations we have made about the relationships between biomechanical forces and glial response and axonal injury. However, further work with gyrencephalic animals such as ferrets or pigs would allow the impact of sulcal anatomy on the relationship between biomechanical forces and brain injury to be studied directly ( Schwerin et al , 2017 , 2018 ; Hutchinson et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not the focus of our research and does not directly impact on the observations we have made about the relationships between biomechanical forces and glial response and axonal injury. However, further work with gyrencephalic animals such as ferrets or pigs would allow the impact of sulcal anatomy on the relationship between biomechanical forces and brain injury to be studied directly ( Schwerin et al , 2017 , 2018 ; Hutchinson et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, further work with gyrencephalic animals such as ferrets or pigs would allow the impact of sulcal anatomy on the relationship between biomechanical forces and brain injury to be studied directly (Schwerin et al, 2017;Hutchinson et al, 2018;Schwerin et al, 2018).…”
Section: Gfap-positive Cellsmentioning
confidence: 99%
“…In a recent ferret model of mTBI, FA reductions in the white matter regions not proximate to the site of impact were most pronounced at later time points (ie, 4-16 weeks). 21…”
Section: Discussionmentioning
confidence: 99%
“…14 Only few DTI studies have proven to reliably detect TBI and approximate time of injury 15 in various rodent models of axonal injury following single or repetitive head impact. [15][16][17][18][19][20][21] Moreover, few studies have assessed the evolution of axonal injury over time following mTBI in rodents. It has been suggested that longitudinal studies are needed to determine how changes in DTI indices are related to recovery in response to concussive injury.…”
Section: Introductionmentioning
confidence: 99%
“…Xtract contains tractography libraries for humans and macaques derived from the same protocols (Warrington et al, 2020) and is currently being extended to include more species, including the chimpanzee (Bryant et al, 2020). AFNI (Cox, 1996) and TORTOISE (Pierpaoli, et al, 2010) have several diffusion processing tools and integrated features for distortion correction (Irfanoglu et al, 2015), deterministic and probabilistic tractography (Taylor and Saad, 2013), tensor-based morphometry (Hutchinson et al, 2018;Irfanoglu et al, 2016), and network-based structural analyses (Taylor et al, 2016b). Additionally, Dipy is a Python-based software toolbox for diffusion processing (Garyfallidis et al, 2014), and DSI-Studio contains tools for tracking and statistics with a particular focus on high angular resolution diffusion imaging (HARDI) techniques (http://dsistudio.labsolver.org).…”
Section: Diffusion-weighted Mri Toolsmentioning
confidence: 99%